THE EFFECT OF SUBTITLED ANIMATED CARTOON VIDEOS ON STUDENTS’ READING COMPREHENSION (A Quasi Experimental Study at The Sixth Grade Students of SDIT Al- Hasanah Kota Bengkulu) - Gustian Pelani (Universitas Bengkulu, 2016)
Thisstudyaims toinvestigatewhetheror nottheuseofsubtitledanimated cartoonvideosaffectstudents’ reading comprehension and to findoutinwhat performanceof reading comprehension aspectstheexperimentaland controlclassdiffer. ThepopulationincludedallthesixthgradestudentsofSDITAlHasanahKotaBengkulu in academic year 2015/2016, which consisted of 77 students. The sampleswere 52 studentsthatwere taken fromtwo classes.Theexperimentalclass receiveda treatmentby usinganimatedcartoonvideoswithbimodalsubtitles, while thecontrolclasswas taught byusinganimatedcartoonvideoswithoutsubtitles.A pre-testwasgiven tobothclasses beforetreatment.Thedata wereanalyzedbyusingSPSS16for t-testformula.Theresults show that, firstly, therewasa statistically significantdifferencebetween thegroups in readingcomprehension scores.Therefore, itwasconcluded thattheuse ofsubtitled animated cartoon videoscould improvestudents’ reading comprehension. Secondly, for reading comprehension aspects, the experimental class and the control class were different inthe literalperformanceaspect.However,intheinferenceperformance,it showed no significant difference. Based on the results, it wasrecommended to use subtitled animatedcartoonvideosastheteaching aidinteachingreadingcomprehension